Farmers' food insecurity coping strategies in the Sidama region of southern Ethiopia. Issue 5 (4th July 2021) - Abebe, Gezahegn
ABSTRACT: The article provides evidence of farmers' food insecurity coping strategies using interviews and household questionnaire methods. Data show that 28% in the Fero-two Peasant Association (PA) and 24% in the Hanja-Chafa PA were severely food insecure. In the respective places 26% and 37% were moderately food insecure and 46% and 40% were food secure. Farmers adopted different consumption-related and other coping strategies to food insecurity originating from social, economic, political, and environmental factors. The findings suggest that policymakers should consider the local features of a given place in designing place-specific policy interventions and resilient adaptation strategies to achieve long-term food security.